Chemical and genetic diversity of Astragalus mongholicus grown in different eco-climatic regions. - Lin Li; Sihao Zheng; Josef A Brinckmann; Juan Fu; Rui Zeng; Linfang Huang; Shilin Chen (PLoS ONE, 2017)
Astragalus mongholicus Bunge (Fabaceae) is an important plant source of the herbal drug known as Radix Astragali, which is used worldwide as a medicinal ingredient and a component of food supplement. Russian Federation, Mongolia, Kazakhstan, and China are the main natural distribution areas of A. mongholicus in the world. However, the quality of medicinal plant varies among different locations. As for A. mongholicus, limited literature focused on its biodiversity mechanism. Here, we combined the chemometric analysis of chemical components with genetic variation, as well as climatic and edaphic traits, to reveal the biodiversity mechanism of A. mongholicus. Results showed that the detected chemical, genetic and climatic traits comprehensively contributed to the quality diversity of A. mongholicus. The eight main chemical components, as well as the inorganic elements of P, B and Na were all significant chemical factors. The precipitation and sunshine duration were the main distinguishing climatic factors. The inorganic elements As, Mn, P, Se and Pb were the distinguishing edaphic factors. The systematic method was firstly established for this medicinal plant in order to illustrate the formation of diversity in terms of quality, and provide scientific evidence for geographic indications and climatic adaptation in production and in the clinical application of herbal medicinal plants.